Stable and efficient hydrogen evolution reaction catalyzed by NiO-Rh2P heterostructure electrocatalyst - Shuyuan Pan; Xinxin Yu; Ying Ling; Zehui Yang (Catalysis Communications, 2022)
A NiO-Rh2P heterostructure electrocatalyst was constructed by phosphating the NiO-Rh structure. Due to the high capability of water dissociation by NiO, only 46 mV overpotential was demanded to achieve 10 mA cm−2 for the NiO-Rh2P, which is 73 mV lower than Rh2P in alkaline HER catalysis. Besides, the strong electronic interplay between NiO and Rh2P also contributed to the robust stability of NiO-Rh2P heterostructure electrocatalyst.